Cycle of coercion: experiences of maltreatment and disciplinary measures in Canadian inmates. Issue 2 (10th June 2014) - Joubert, David; Archambault, Kyle; Brown, Greg
Abstract : Purpose: – In spite of past and current efforts at implementing effective rehabilitative interventions in carceral settings, institutions of confinement are primarily concerned with the maintenance of order within their walls. The purpose of this paper is to better understand associations between inmates' developmental background and the experience of institutional discipline, to collect information on childhood maltreatment and disciplinary measures for a sample of Canadian prisoners. Design/methodology/approach: – Information relative to socio-economic background, childhood maltreatment and experience of discipline while in custody was obtained using face-to-face interviews and institutional file review for a sample of 416 male and 106 female offenders in Canadian provincial institutions. Findings: – Results from logistic regression analyses provided support for the association between childhood maltreatment and the experience of discipline, specifically in the form of increased monitoring from correctional staff. Furthermore, this association was found to be more pronounced for female offenders. Research limitations/implications: – The findings highlight the need to incorporate a developmental perspective to current understanding of the use of disciplinary interventions in a prison environment. Such an approach may allow for preventing the enactment of a cycle of coercion, with negative consequences for the inmates. Originality/value: – This study is original in its use of latent variable analytic methods to uncover the structure underlying the construct of childhood maltreatment in adult offenders. In addition, it provides valuable data of interest to researchers, corrections personnel and policy makers on the possible links between earlier developmental experiences and adjustment to the prison environment.